Evaluasi Manajemen Risiko Dalam Penerapan Kebijakan Restrukturisasi Saat Pandemi Covid-19 Pada Bank ABC. - Divayanti Sabrina Rosadi; Ludovicus Sensi Wondabio (Jurnal Ilmiah Wahana Pendidikan, 2023)
Banking which has a role as a source of financing for the community facesmany risks, one of which is credit risk. This risk possibility was increased,especially during the COVID-19 pandemic, which caused uncertainty onthe economic circumstances and conditions. For this reason, the FinancialServices Authority (OJK) issued the POJK RI Number 11/POJK.03/2020concerning National Economic Stimulus as a Countercyclical Policy whichunderwent two amendments, namely POJK Number 48/POJK.03/2020 andPOJK Number 17 /POJK.03/2021. Bank is expected to capable in identifythe risks it faces and establish comprehensive mitigations to ensure itsobjectives can still be achieved. The purpose of this study is to evaluateBank ABC's credit risk management policies related to the implementationof the Countercyclical Policy from OJK. This research is a case studyconducted in qualitative research methods through interviews and analysisof Bank's Internal Policy Documents and Annual Reports. The result showsthat Bank ABC undergo a credit risk management policy. Despite the factsthere are still weaknesses, Bank ABC has implemented credit riskmanagement principles according to the framework and regulations inforce. Evidently, its implementation has a positive impact on the bank'sfinancial performance in 2021, such as NPL and CAR